A comparative study of radiocarbon dating on terrestrial organisms and fish from Qinghai Lake in the northeastern Tibetan Plateau, China. (November 2018) - ChongYi, E; Sun, YongJuan; Liu, XiangJun; Hou, Guangliang; Lv, ShunChang; Yuan, Jie; Sun, Manping
Qinghai Lake is the largest lake on the Tibetan Plateau (TP) and in China and has been a focus of paleoenvironmental and climatic research for decades. However, limited understanding of lake 14 C reservoir effects (LRE) has led to inconsistent interpretations among proxies of different sediment cores. As such, the onset of LRE variability during the Holocene is still unclear. 14 C dating of archeological samples from four locations (Gangcha, Shaliuheqiaoxi, and Shinaihai sites, and Niaodao section) including naked carp ( Gymnocypris przewalskii, Kessler) fish bones, animal bones and teeth, and charcoal was employed to estimate variations in LRE over the last few thousand years. LRE offsets calculated as the difference between LRE of animal bones and fish bones are more reliable than that of charcoal and fish bones due to the 'old wood' effect in charcoal. LRE offsets recorded in fish bones were 0.5, 0.6, and 0.7 ka during the periods of 3.0–3.4 cal ka BP, 0.58–0.60 cal ka BP, and modern lake times, respectively, which may indicate a temporal minimum LRE offset. Unlike the wide spatial variations of LRE ages obtained from surface total organic carbon (TOC) samples of the modern Qinghai Lake, LRE offsets from the three contemporaneous locations in Qinghai Lake were all 0.5 ka, suggesting efficient carbon mixing occurred in naked carp. However, the late-Holocene ( 3.1 ka BP) LRE increased slightly with increasing salinity and decreasing lake level.